Video feedback at sport events - Sfingos, N.; Tsamourtzis, E.; Tsimpiris, A. (World Congress of Performance Analysis of Sport VIII, 2008)
As a result an interactive and user-friendly application attached in a video database of 3.360 hours captured video was developed giving the ability of immediate video feedback, of scenes or photo material saving and of ordering authored VCD. We also create a tool by SQL queries for information extraction about statistics like the distribution of sport categories that used this service. Data analysis summarized and presented in the form of charts and data reports. The service being on line 16 hours per day and covering 37 categories of Olympic sports proved as a significant tool for 12.741 individual or team requests. In addition during the 16 days of the Olympic Games, video editing of 10.000 ordered VCD`s of various sport events, processed and completed successfully. The above services together with the fully functional digital video database were provided for the first time in the Olympic Games history. The need of utilizing such services and applications during sport events is growing and is eventually necessary. The events are stored in digital video with all the benefits of this and can be used for further educational, research, historical or other plans. Similar services could be used for almost every athletic event.